Protection of vascular barrier integrity by activated protein C in murine models depends on protease-activated receptor-1 - Schuepbach, Reto A.; Feistritzer, Clemens; Fernández, José A.; Griffin, John H.; Riewald, Matthias (Thrombosis and Haemostasis, 2009)
Protease activated receptor-1 (PAR1) mediates barrier protective signalling of activated protein C (APC) in human endothelial cells in vitro and may contribute to APC’s beneficial effects in patients with severe sepsis. Mouse models are of key importance for translational research but species differences may limit conclusions for the human system. We analysed whether mouse APC can cleave, activate and induce signalling through murine PAR1 and tested in newly established mouse models if long-term infusion of APC prevents from vascular leakage. Cell surface immunoassays demonstrated efficient cleavage of endogenous murine endothelial PAR1 by either murine or human APC. Pharmacological concentrations of APC of either species had powerful barrier protective effects on cultured murine endothelial cells that required PAR1 cleavage. Vascular endothelial growth factor-mediated hyperpermeability in the skin was reduced by either endogenously generated as well as directly infused recombinant mouse APC in wild-type mice. However APC did not significantly alter the vascular barrier function in PAR1-deficient mice. In endotoxin-challenged mice, infused APC significantly prevented from pulmonary fluid accumulation in the wild-type mice but not in mice lacking PAR1. Our results directly show that murine APC cleaves and signals through PAR1 in mouse endothelial cells. APC reduces vascular permeability in mouse models and PAR1 plays a major role in mediating these effects. Our data in vitro and in vivo support the paradigm that PAR1 contributes to protective effects of APC on vascular barrier integrity in sepsis.
Keywords: Activated protein C; endothelial cells; protease-activated receptor-1; sepsis; vascular barrier